Insights from the supplementary motor area syndrome in balancing movement initiation and inhibition - Potgieser, A. R. E.; de Jong, B. M.; Wagemakers, M.; Hoving, E. W.; Groen, R. J. M. (Frontiers in Human Neuroscience, 2014)
The supplementary motor area syndrome is a characteristic neurosurgical syndrome that can occur after unilateral resection of the supplementary motor area. Clinical symptoms may vary from none to a global akinesia, predominantly on the contralateral side, with preserved muscle strength, and mutism. A remarkable feature is that these symptoms completely resolve within weeks to months, leaving only a disturbance in alternating bimanual movements. In this review we give an overview of the old and new insights from the supplementary motor area syndrome and extrapolate these findings to seemingly unrelated diseases and symptoms such as Parkinson’s disease and tics. Furthermore, we integrate findings from lesion, stimulation and functional imaging studies to provide insight in the motor function of the supplementary motor area.